2006
DOI: 10.1086/500934
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Death Due to Invasive Aspergillosis after Hematopoietic Stem Cell Transplantation: A 1-Year Retrospective Study of Consecutive Patients at French Transplantation Centers

Abstract: The proportion of deaths attributed to IA within 4 months after diagnosis was 0.62 (95% confidence interval, 0.47-0.76). Seven factors assessed at diagnosis were determined to be strongly related to death due to IA: age of 12-35 years, dissemination of IA, presence of a pleural effusion, monocyte count of <120 cells/mm3, prolonged administration of steroids within the previous 2 months, receipt of a dose > or =2 mg/kg at the time of diagnosis, and uncontrolled graft-versus-host disease.Conclusions. Our study e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
94
0
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(110 citation statements)
references
References 13 publications
11
94
0
5
Order By: Relevance
“…2,4,6,18 In addition, analyses of prognostic factors verify the other previously recognized important prognostic factors (uncontrolled GVHD, steroids dose). 2,4,7,19,20 There are few reports on the long-term survival (≥ one year) of allogeneic HSCT recipients with IA. The overall one-year survival rate was 20% for Seattle IA patients receiving transplants between 1993 and 1998, while survival was only 7% for the cohort receiving transplants between 1987 and 1993.…”
Section: Discussionmentioning
confidence: 99%
“…2,4,6,18 In addition, analyses of prognostic factors verify the other previously recognized important prognostic factors (uncontrolled GVHD, steroids dose). 2,4,7,19,20 There are few reports on the long-term survival (≥ one year) of allogeneic HSCT recipients with IA. The overall one-year survival rate was 20% for Seattle IA patients receiving transplants between 1993 and 1998, while survival was only 7% for the cohort receiving transplants between 1987 and 1993.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the first peak is less significant because of the routine use of stem cells instead of bone marrow for transplantation, nonmyeloablative regimens, the use of colonystimulating factors during neutropenia and the widespread use of antifungal agents [13,26]. The second peak has become more significant, especially with the higher incidence of GVHD associated with unrelated allogeneic transplantation and treatment with intensive immunosuppressive therapy, including corticosteroids, cyclosporine A, anti-TNF agents, and other T-cell depleting strategies [13,14,17,[27][28][29].…”
Section: Risk Factorsmentioning
confidence: 99%
“…IFIs have a high attributable mortality despite appropriate antifungal treatment. [1][2][3][4] Non-myeloablative or reduced-intensity conditioning (RIC) results in less severe mucositis and a shorter period of neutropenia after HSCT. This has reduced the incidence of early bacterial infections, but some studies have shown that the incidence of IFI after RIC is the same or even higher than with myeloablative regimens.…”
Section: Introductionmentioning
confidence: 99%